Influence of Stirring Speed on Mechanical Properties for Cast Nano-Particulate AA7075-Al2O3 Composites - Alalkawi, H. J. M.; Mohammed, Asifa Mahdi; Majid, Raad Hameed (Al-Nahrain Journal for Engineering Sciences, 2019)
Aluminum metal matrix composites are widely employed for improving the mechanical properties. Various fabrication routes like liquid state, solid state and liquid-solid state are currently available for producing these materials. The objective of the present work is the fabrication of nano particulate composites AA7075-Al2O3 with different amount of nano particles (20-30 nm) reinforced material Al2O3 (2, 4 and 6 wt%) using stir casting technique at three stirring speeds (300, 850 and 1500 rpm). Tensile tests of these composites were carried-out to obtain the mechanical properties (ultimate strength and ductility). Vickers hardness tests were also performed to obtain the hardness number (VHN) of these materials. All tests were performed at room temperature. The microstructures of the best mechanical properties’ composites were examined for the three stirring speeds. It was revealed that the ultimate strength (?u) and Vickers hardness (VHN) for the composite containing 6 wt% Al2O3 fabricated at 850 rpm show the best properties compared to the other composites fabricated at 300 and 1500 rpm and the matrix. The ?u and VHN were increased by about (36.6 %) and (24.5 %) respectively. Ductility of the strongest composite (6 wt% Al2O3 at 850 rpm speed), however, was the least when compared to other composites and the matrix. With increasing the amount of Al2O3, ?u and VHN, an increasing trend was noticed while the ductility shows a reduction trend. The maximum reduction in ductility occurred for the composite containing 6 wt% Al2O3 obtained at 850 rpm. The ductility of the developed composite was reduced by (23 %). The optical microstructures of unreinforced, as-cast Aluminum alloy AA7075 and 6 wt% Al2O3 composites for all stirring speeds show dendrite microstructure resulting from the casting process, but the composite at the stirring speed of 850 rpm shows a more refined microstructure.